The Development of Russian-Chinese Relations: Prospects for Cooperation in Crisis - Grigorenko, Olga V.; Klyuchnikov, Denis A.; Gridchina, Aleksandra V.; Litvinenko, Inna L.; Kolpak, Eugeny P. (International Journal of Economics and Financial Issues, 2016)
In the context of the global economic crisis and the trend towards deterioration of relations between Russia and the Russian-Chinese cooperation with Western countries it is one of the most promising areas of Russian foreign policy. China in recent history becomes more and more powerful geopolitical player in the world and try to take as much as possible an active part in world affairs. China's participation in organizations such as the UN, APEC, SCO, BRICS, etc. allowing it to implement its national interests. As a global trading power, and based on his potential and its intensified role on the world stage, China is forming a new foreign policy. As is known, Russia and China are now solved similar problems is “the transition to an innovative model of development” (Russia) and the “creation of the state of innovative type” (China). The modernization of the Russian economy requires a major upgrade production facilities and the development of transport infrastructure, largely due to large-scale foreign investment and the import of modern technologies. Part of the problem can be solved with the help of China, which is the world leader in terms of gold reserves and constantly increases the volume of its foreign investments. In our view, the prospects for the development of Russian-Chinese relations in the bilateral economic cooperation are, above all, in the initiation and development of major projects. The key point of the Russian-Chinese economic relations should also be cross-border cooperation. Keywords: world financial crisis, Russian-Chinese relations, innovative development, trade cooperation, economic cooperation JEL Classification: G01, O31, P13